Population Pharmacokinetics and Dosage Optimization of Teicoplanin in Children With Different Renal Functions - Gao, Liuliu; Xu, Hua; Ye, Qi; Li, Sichan; Wang, Jun; Mei, Yan; Niu, Changhe; Kang, Ting; Chen, Chen; Wang, Yang (Frontiers in Pharmacology, 2020)
Objective: The purposes of our study were to investigate the population pharmacokinetics of teicoplanin in Chinese children with different renal functions and to propose the appropriate dosing regimen for these pediatric patients. Methods: We performed a prospective pharmacokinetic research on children aged 0-10 years, with different renal functions. The population pharmacokinetics model of teicoplanin was developed using NLME program. The individualized optimal dosage regimen was optimized on the basis of the obtained population pharmacokinetics parameters. Results: To achieve the target trough level of 10-30 mg/L, optimal dosing regimen for children with different renal functions are predicted as follows based on the population PK simulations: children with moderate renal insufficiency need three loading doses of 6 mg/kg q12h followed by a maintenance dose of 5 mg/kg qd; children with mild renal insufficiency require three loading doses of 12 mg/kg q12h followed by a maintenance dose of 8 mg/kg qd; children with normal or augmented renal function should be given three loading doses of 12 mg/kg q12h followed by a maintenance doses of 10 mg/kg qd. Conclusion: The first study on the population pharmacokinetics of teicoplanin in Chinese children with different renal functions was performed. Individualized dosing regimen was recommended for different renal function groups based on population PK model prediction.